1999
DOI: 10.1042/bj3430095
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribosylation) protects maternally derived histones from proteolysis after fertilization

Abstract: Fertilization in sea urchins is followed by the replacement of sperm-specific histones by cleavage-stage histone variants recruited from maternal stores. Such remodelling of zygote chromatin involves a cysteine proteinase that degrades the sperm-specific histones in a selective manner, leaving the maternal cleavage-stage histone variants intact. The mechanism that determines the selectivity of the sperm-histone-selective proteinase (SpH-proteinase) was analysed by focusing on the post-translational modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…This protease degrades sperm histones leaving the maternal CS histone variants intact [Imschenetzky et al, 1997]. The protection of CS histone variants against proteolysis is due to their extensive poly(ADP-ribosylation) [Morin et al, 1999a]. Alternatively, we have also demonstrated that sperm specific histones H1 and H2B are protected against this protease by their phosphorylation [Morin et al, 1999b].…”
mentioning
confidence: 85%
“…This protease degrades sperm histones leaving the maternal CS histone variants intact [Imschenetzky et al, 1997]. The protection of CS histone variants against proteolysis is due to their extensive poly(ADP-ribosylation) [Morin et al, 1999a]. Alternatively, we have also demonstrated that sperm specific histones H1 and H2B are protected against this protease by their phosphorylation [Morin et al, 1999b].…”
mentioning
confidence: 85%
“…Interestingly, it was demonstrated that this substrate selectivity is mainly determined by the poly(ADP-ribose) moiety present in the CS variants, as only the modified proteins were protected from degradation (Morin et al, 1999a). It was also found that phosphorylation of SpH1 and SpH2B histones protect them from degradation (Morin et al, 1999b).…”
Section: Role Of Proteolysis In Chromatin Remodeling Of the Male Pronmentioning
confidence: 97%
“…Furthermore, we have identified a nuclear cysteine-protease that degrades the SpH leaving the maternal CS histones unaffected [Imschenetzky et al, 1997]. The activity of this enzyme is modulated by post-translational modifications of its substrates, phosphorylation protects SpH1 and SpH2B from degradation [Morin et al, 1999a], and poly(ADP-ribosylation) blocks the proteolysis of CS histone variants [Morin et al, 1999b]. It is unknown yet if this protease may catalyze the degradation of the SpH while these histones are organized as nucleosome cores, or if the SpH should be removed before degradation.…”
mentioning
confidence: 98%